Hubungan Sikap Dan Praktik Ibu Selama Program Pemberian Makanan Tambahan Terhadap Status Gizi Balita Di Wilayah Kerja Puskesmas Sidoharjo Kabupaten Sragen - ARDIANA, FETY; , Dr. Mutalazimah, SKM, M.Kes; , Muwakhidah, SKM, M.Kes (2015)
Background :The nutritional status is a body condition as a result of balancing interaction nutritional subtance to the body's needs, which are known by measurement of a variable and classified into categories of specific nutritional. Children under five with malnutrition based on Weight and Height is a condition where a Z-score ≥-3SD <-2SD with clinical signs look thin. Nutritional status of children under five years old influenced by direct and indirect factor. The one of direct factor is food consumption. Food consumption related mother's knowledge that influential on mother's attitude and practice. Objective : To know the relationship between the mother's attitude and practice during Suplementary Feeding's Programme toward Nutritional state of children under five years old in Sidoharjo Health. Methods : Type of research that used in this research is observational. The sampling are mothers who have children under five years old with malnutrition targeting on Suplementary Feeding's Programme to the total of 33 children. Mother's attitude and practice of mothers was obtained by filling the questionnaire, while the nutritional status of children under five years old was obtained by measuring the Weight and Height. Result : A total of 75.8 % nutritional state of children under five years old are increase and 24.2 % are not increase. A total of 42,4 % show mother's attitude are supporting and 57.6 % are not supporting. A total of 60.6 % mother's practice are good and 39.4 % unfavorable. The result of research was tested by paired sample t-test show there is effect of Suplementary Feeding's Programme toward the nutritional status of children under five years old (p=0.00). The results of Spearman Rank correlation test show there is no relationship between the mother's attitude with nutritional status of children under five years old (p = 0.159). There is no relationship between mother's attitude and nutritional status of children under five years old (p = 0.333). Conclusion :Suplementary Feeding's Programme increase the nutritional status of children under five years old. There is no important relationship of mother's attitude and practice during Suplementary Feeding's Programme toward children under five years old. Keywords :nutritional status, children under five years old, mother's attitude, mother's practice Bibliography : 1993-2015